2017
DOI: 10.1186/s12906-017-1653-z
|View full text |Cite
|
Sign up to set email alerts
|

How do medical students engaging in elective courses on acupuncture and homeopathy differ from unselected students? A survey

Abstract: BackgroundWe aimed to investigate whether students at German medical schools participating in elective courses on acupuncture and homeopathy differ from an unselected group of students regarding attitudes and personality traits.MethodsElective courses on acupuncture and homeopathy in the academic half-year 2013/14 all over Germany were identified and participants invited to fill in a questionnaire including nineteen questions on attitudes towards Complementary and Alternative Medicine (CAM), orientation toward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 22 publications
2
13
0
2
Order By: Relevance
“…Assuming that, in our survey, we included 80% of all German students participating in an elective course on acupuncture or homeopathy in our sampling period, we estimate that 5-10% of all German medical school students participate in such courses during their study. The proportion of 9% of students reporting current or past participation in an elective course in the unselected control group in the other part of our study [11] also fits with such an estimate. Acupuncture/Traditional Chinese Medicine and homeopathy are the CAM therapies most often taught at German medical schools, but we know of a number of broader CAM courses, courses focusing on 'natural healing procedures' (focusing on herbal medicine, lifestyle, etc.)…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Assuming that, in our survey, we included 80% of all German students participating in an elective course on acupuncture or homeopathy in our sampling period, we estimate that 5-10% of all German medical school students participate in such courses during their study. The proportion of 9% of students reporting current or past participation in an elective course in the unselected control group in the other part of our study [11] also fits with such an estimate. Acupuncture/Traditional Chinese Medicine and homeopathy are the CAM therapies most often taught at German medical schools, but we know of a number of broader CAM courses, courses focusing on 'natural healing procedures' (focusing on herbal medicine, lifestyle, etc.)…”
Section: Discussionsupporting
confidence: 83%
“…Personal experiences and influence of the family or the personal environment have been shown to be important both among students [13] and physicians practicing CAM [15]. The other part of our project showed that, compared to unselected students, participants in elective courses of acupuncture and homeopathy -apart from having more positive attitudes towards CAM -were more critical about science and had a higher social and a lower status orientation [11].…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…The former had low interest in status (i.e., social reputation and income) as a driver in the decision to be a medical doctor and were more likely to be destined for family medicine. Among those who were not inclined, a sub-group of students (about 1/4 of 315 students) were identifiable by overt objections to traditional medicine perspectives; these latter students scored high on status motivations and low on agreeableness [160]. Agreeableness is negatively correlated with authoritarianism, SDO and Machiavellianism [161,162].…”
Section: Tollo Causa: Research Questions and Future Directionsmentioning
confidence: 99%